2018
DOI: 10.1002/mbo3.619
|View full text |Cite
|
Sign up to set email alerts
|

Removal and biodegradation of different petroleum hydrocarbons using the filamentous fungus Aspergillus sp. RFC‐1

Abstract: Petroleum pollution inevitably occurs at any stage of oil production and exerts a negative impact on the environment. Some microorganisms can degrade petroleum hydrocarbons (PHs). Polluted sludge of Rumaila oil field was use to isolate the highly efficient hydrocarbon‐degrading fungal strain. Aspergillus sp. RFC‐1 was obtained and its degradation ability for petroleum hydrocarbons was evaluated through surface adsorption, cell uptake, hydrophobicity, surface tension, biosurfactant produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(36 citation statements)
references
References 61 publications
2
33
0
1
Order By: Relevance
“…The ability of this species to produce more than one type of degradative enzyme in high quantities may increase its potential to degrade PAH compounds (Barnes et al, 2018; Mohsenzadeh et al, 2012). These results are consistent with those of other studies in which fungi especially the genus Aspergillus has a great degradation ability for hydrocarbons (Al‐Hawash et al, 2018; Ponnapalli et al, 2018; Ye et al, 2011).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The ability of this species to produce more than one type of degradative enzyme in high quantities may increase its potential to degrade PAH compounds (Barnes et al, 2018; Mohsenzadeh et al, 2012). These results are consistent with those of other studies in which fungi especially the genus Aspergillus has a great degradation ability for hydrocarbons (Al‐Hawash et al, 2018; Ponnapalli et al, 2018; Ye et al, 2011).…”
Section: Resultssupporting
confidence: 93%
“…corresponding to 92.41% degradation (Figure 3). This finding is consistent with that of several studies (Al‐Hawash et al, 2018; Govarthanan et al, 2017; Hamzah et al, 2012), which reported that the optimum temperature for fungal growth during the oil degradation processes was 30°C. This may be because of an increase in fungal growth, which potentially improved energy efficiency in the system by facilitating contact between the cell surfaces and the energy source.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The first mechanism promotes the emulsification of hydrophobic compounds to mycelial pellet structures. The second mechanism induces high cell surface hydrophobicity, thus increasing the direct physical contact between cells and poor water-soluble substrates [38,39].…”
Section: Biodegradation Of Crude Oil By Two Fungal Isolates And/or Agnpsmentioning
confidence: 99%